(untitled) (Yesterday & Today Journal for History Education in South Africa and abroad, 2022)
This study attempted to capture stakeholders’ views on the school history curriculum in Zambia. Stakeholders’ views are an important aspect of curriculum development. Social media such as Facebook and WhatsApp have become platforms a section of Zambians uses to challenge the traditional education system. The study used a qualitative approach design by monitoring the e-comments of focus groups (teachers’ forums) and individuals on Facebook on what some Zambians thought about the history curriculum. Social media was used because it provides an environment that removes traditional inhibitions of authority figures and meets people in their comfort zone, making them free to discuss otherwise sensitive topics. This research revealed that various stakeholders found the curriculum content irrelevant to the future they envisioned for themselves. The study additionally found that people in Zambia had been side-lined in discussions concerning curriculum development for history. People felt that they had been placed into the straitlaced role of consumers, and their feedback has never been sought. The study recommends revisiting the school history curriculum content to reflect stakeholders’ needs and apply it to society. Curriculum developers should also pay attention to the voices of stakeholders in society.